Temporal Evolution of Island Arc Magmatism and Its Influence on Long-Term Climate: Insights From the Izu Intra-Oceanic Arc - Ribeiro, Julia M.; Ishizuka, Osamu; Pogge von Strandmann, Philip A. E.; Tamura, Yoshihiko; Xu, Yi-Gang (Frontiers in Earth Science, 2022)
Continental arcs have an episodic magmatic activity over long-time periods, which is believed to modulate long-term climate. Island arcs have also the potential to release large amount of CO2 into the atmosphere, but whether they display an episodic magmatic history throughout their lifespan that contributes to the long-term (≥ 10 Ma) climate changes remains an open question. To set additional constraints on the magmatic history of island arcs, here we examine fresh basalts and mineral-hosted melt inclusions from the Izu intra-oceanic arc, shortly after the eruption of boninites (~ 45 Ma ago). Using chemical markers, we show that the long-term magmatic activity of the mature Izu arc has been relatively continuous, except during opening of the Shikoku back-arc Basin (~ 23 – 20 Ma). Because slab dehydration and slab melting trigger decarbonation and carbonate dissolution of the subducted plate, we use slab-fluid markers (Ba/Th, Cs/Th, Cs/Ba, Rb/Th, Th/Nb) to examine the variations of slab-derived CO2 captured by the arc magmas. The long-term steadiness in the magmatic activity and in the slab-fluid contribution in the Izu arc suggests that the CO2 outgassed during arc volcanism has remained relatively homogeneous for the past 40 Ma. If worldwide mature island arcs maintain a steady state, the long-term CO2 outgassed by these volcanoes may be rapidly balanced by chemical weathering and tectonic erosion, which rapidly draw down the atmospheric CO2 (within 200 - 300 kyr). This rapid negative feedback to volcanic degassing permits to sustain a viable atmospheric CO2 for millions of years. The lack of co-variations between the markers of climate changes (delta13O, delta13C) and the long-term averages of the markers of slab fluids and magmatic activity further implies that volcanic degassing of CO2 from mature island arcs might play a minor role in the slide into icehouse climatic conditions. This degassing stability may be, instead, a contributor to maintaining a broadly stable climate over long timescales.